Ethics, governance and consent in the UK: implications for research into the longer-term outcomes of congenital heart defects. Issue 1 (21st September 2009) - Knowles, Rachel L; Bull, Catherine; Wren, Christopher; Dezateux, Carol
Abstract : Objective: To explore the effect of research ethics, governance and consent requirements and recent reforms on UK-wide follow-up of children with congenital heart defects (CHD). Design: Prospective cohort study. Setting: UK National Health Service. Patients: 3897 children with CHD requiring intervention, or resulting in death, before they were 1-year-old (1993–1995). Main outcomes: Impact on study protocol, timeliness and findings of a multicentre study of survival and quality of life. Results: The peer-reviewed study protocol was altered to accommodate ethics committee stipulations that researchers should not approach families directly with a request to participate and that the general practitioner's (GP) permission be sought before the local clinician could do so. Individual consent was required to confirm the vital status of participants and for future tracing of public death registrations. Local study registration took a median of 40 weeks (IQR 25–57). 180 (24%) of 739 surviving children (five centres) could not be contacted because their GP was untraceable (32), had changed (128) or considered contact inappropriate (20). Invitations could not be sent to 31% from the most deprived compared with 17% from the least deprived areas. Conclusions: Decision making concerning childhood interventions should be influenced by evidence on long-term outcomes. However, current UK research regulations hinder follow-up in multicentre studies. Stipulations preventing researchers contacting families directly with research invitations appear disproportionate to the risks, impede equitable access to research opportunities and introduce bias. The requirement for an individual's consent to confirm whether they are alive and monitor survival precludes effective long-term follow-up.